Hubungan Malaria Dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan Di Wilayah Kerja Puskesmas Marauw Kabupaten Biak Numfor - Ika Wijayanti; Endang Trisnawati; Diana Maryen (Kementerian Kesehatan Poltekkes Malang, 2026)
Background: Stunting is a global nutritional problem. Within the first 1,000 days of life (HPK), children are vulnerable to stunting, which can impact their growth. Frequent infectious diseases in toddlers are closely linked to suboptimal growth, thus contributing to stunting. Malaria is a direct cause of malnutrition in children and vulnerable populations. The purpose of this study was to determine the relationship between malaria and stunting in toddlers aged 24-59 months in the Marauw Community Health Center (Puskesmas) working area, Biak Regency. Research Method: This study used a quantitative cross-sectional design. The population was all toddlers with stunting and toddlers with a history of malaria aged 24-59 months within the Marauw Community Health Center working area. A total sampling technique was used to select 84 samples. The statistical test used was the chi-square test. Research results: There is a relationship between malaria and stunting in toddlers aged 24-59 months in the Marauw Community Health Center working area, Biak Regency, with a p-value of 0.015. Conclusion: This study concludes that there is a relationship between malaria and stunting in toddlers aged 24-59 months in the Marauw Community Health Center working area, Biak Regency.